Integrated design and optimization research of LNG cold energy and main engine exhaust heat utilization for LNG powered ships - Shou-guang Yao; Zijing Zhang; Yue Wei; Rui Liu (Case Studies in Thermal Engineering, 2022)
This paper aims at the high-efficiency utilization of LNG cold energy and main engine exhaust heat of ten-thousand-box LNG-powered container ship, and takes the 9200TEU LNG powered ship as the target ship. The two-level parallel Rankine cycle system is used to replace the original exhaust heat boiler utilization system, and the LNG horizontal three-level nested Rankine cycle is added on the basis of the two-level parallel Rankine cycle, realizing the efficient integrated utilization of the LNG vaporization cold energy and the exhaust heat of the main engine. Aspen HYSYS is used to simulate the scheme, and the genetic algorithm is further used to optimize the parameter matching of the system. Finally, the economic analysis of the cost saved by the optimization scheme and the initial investment cost is carried out. The results show that the system exergy efficiency in summer conditions reaches 58.20%, and the system exergy efficiency in spring, autumn and winter conditions reaches 58.73%; the initial system equipment cost is US$34.41 million, the power production cost of the system is 0.129 US$/kWh, and the payback period PBP is 7.37 years.